Lawsonia intracellularis-associated ulcerative and necro-hemorrhagic enteritis in 5 weanling foals - Arroyo, Luis G. (Canadian Veterinary Medical Association, 2013)
This report describes 5 cases of fatal Lawsonia intracellularis-associated ulcerative and necro-hemorrhagic enteritis in weanling Thoroughbred and Standardbred foals. The lesions are similar to those of the L. intracellularis-associated ulcerative and necro-hemorrhagic enteritis syndrome in pigs. Two foals had concurrent severe typhlo-colitis as a result of a large burden of encysted cyathostomes. The clinical, diagnostic, and therapeutic challenges, and the potential complications encountered during the management of such cases are discussed.